The Impact of Surroundings on the Characters in Thomas Hardy’s Novels - Rahman, Suzana; Muntiningsih, Ratna (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2016)
The  THE  IMPACT  OF  SURROUNDINGS  ON  THE  CHARACTERS  INTHOMAS HARDY’S NOVELS” is to apply the writers’ knowledge on literature and toshow    their  interest  in    reading  novels.  The  writers transfered not  only    their limitedknowledge in analysing novels as literary works but also building the awareness of theimportance of reading habit  to their students of Unswagati because all of them take thesubject  of  Introduction  to English  Literature.    Reading  and  analyzing  novel  is  reallybeneficial  for  students that    both  can  improve  the  students  reading  skill  but  also  theirEnglish  ability,  moreover,  they  will  have  the  ability  in  criticizing  the  novel  fromdifferent  views.  In  brief,  it  will  also  improve  their  critical  thinking. Afterwards,  bydescribing the  characters  and  their  attitudes  toward  each  other  and  how  thesurroundings influence them, we also learn about their culture. The theory that is usedin analysing those novels is from Harvey, Murphy, Klarer, and Lodge. The method thatis applied in analysing the characters and the surroundings is descriptive qualiative inwhich the writers take the data by reading the three novels, explain in details about thecharacters  and  the  surroundings  involved  in  the  story and  some  other  elementssupported the completeness of the story.